2017
DOI: 10.1093/hmg/ddx128
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass and obesity-associated (FTO) protein regulates adult neurogenesis

Abstract: Fat mass and obesity-associated gene (FTO) is a member of the Fe (II)- and oxoglutarate-dependent AlkB dioxygenase family and is linked to both obesity and intellectual disability. The role of FTO in neurodevelopment and neurogenesis, however, remains largely unknown. Here we show that FTO is expressed in adult neural stem cells and neurons and displays dynamic expression during postnatal neurodevelopment. The loss of FTO leads to decreased brain size and body weight. We find that FTO deficiency could reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
226
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(236 citation statements)
references
References 53 publications
9
226
1
Order By: Relevance
“…Interestingly, FTO constitutive knockout mice exhibit an impairment in spatial learning tasks (Li et al . ). This is not surprising given the developmental effect displayed in the FTO knockout mouse.…”
Section: Physiological Importance Of M6a In the Central Nervous Systemmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, FTO constitutive knockout mice exhibit an impairment in spatial learning tasks (Li et al . ). This is not surprising given the developmental effect displayed in the FTO knockout mouse.…”
Section: Physiological Importance Of M6a In the Central Nervous Systemmentioning
confidence: 97%
“…Notably, FTO has been shown to be required for neural differentiation (Li et al . ), adipogenesis (Zhao et al . ; Zhang et al .…”
Section: The M6a‐machineriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, FTO association to obesity may predispose individuals to T2D. Recent studies indicate that FTO may play a role in neurogenesis (Li et al, ) and myogenesis (Wang et al, ), both of which are also affected in diabetes. Further studies are needed to characterize the contribution of FTO to diabetic complications including neuropathy, nephropathy, and myopathy (Table ).…”
Section: Rbps Implicated In Diabetesmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) is one of the most common modification in mRNA, rRNA, tRNA, microRNA and long noncoding RNA (2,3). More recently, it has been reported that the m 6 A methylation plays important roles in the regulation of the circadian clock, meiosis, mRNA degradation and translation as well as microRNA processing (3–7), and moreover, dysregulation of this modification is linked with cancer (8) as well as neurogenesis, learning and memory (9). …”
Section: Introductionmentioning
confidence: 99%